The Influence of Financial Technology and Financial Literacy on MSME Performance in the Madura Region with Financial Inclusion as a Mediating Variable - Hasanah Hasanah; Moh. Zaki Kurniawan (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of Financial Technology (FinTech) and Financial Literacy on Micro and Small Enterprise (MSE) Performance in Sampang Regency, Madura, with Financial Inclusion as a mediating variable. The research was conducted to address the limited understanding of how FinTech adoption and financial literacy interact to enhance MSME competitiveness in developing regions. Using a quantitative approach and survey method, data were collected from 99 respondents selected through purposive sampling among MSEs actively using digital financial services. Data analysis employed path analysis to examine direct and indirect relationships among Financial Technology (X1), Financial Literacy (X2), Financial Inclusion (Z), and MSME Performance (Y). The results revealed that FinTech does not have a significant positive effect on Financial Inclusion, while Financial Literacy significantly improves it. FinTech positively and significantly affects MSME Performance, whereas Financial Literacy does not. Furthermore, Financial Inclusion significantly influences MSME Performance but only mediates the relationship between Financial Literacy and Performance not between FinTech and Performance. These findings underscore the importance of improving financial literacy and optimizing FinTech utilization to strengthen MSME competitiveness and foster inclusive regional economic development.